Librarians and instructors developing student learning outcomes: Using frameworks to lead the process. Issue 3 (5th August 2014) - Lundstrom, Kacy; Anna Fagerheim, Britt; Benson, Elizabeth
Abstract : Purpose: – The purpose of this paper if to design a workshop that effectively facilitates the collaborative revision of student learning outcomes based on current research relating to competencies in information literacy (IL). Design/methodology/approach: – This case study describes collaborations between librarians and writing instructors throughout an eight-week workshop. The workshop focused on using the results of assessments to revise learning outcomes and restructure instruction practices to help students in the areas they struggle with the most. Three significant frameworks, including threshold concepts, backward design and decoding the disciplines, were used to facilitate effective discussion and revise learning outcomes. Findings: – The structure of the workshop based on three key frameworks stimulated innovation, fostered collegiality, prompted future collaborative opportunities and garnered buy-in for the importance and implementation of IL initiatives. This collaboration served as a pilot workshop for future plans to write and revise IL outcomes with other departments across campus. Practical implications: – This study can serve as a model for future collaborations with any department faculty, especially when IL learning outcomes need to be articulated or revised. The frameworks described are particularly helpful for guiding this process. Originality/value: – While much is written on librarian collaborations, this case study emphasizes the importance of creating even closer collaborative opportunities that place both non-library faculty and teaching librarians on equal footing, allowing everyone in the workshop to take part in the design and implementation of integrating IL into a program. It also gives concrete ways to use threshold concepts to discuss IL issues with faculty, which is a major focus of the newly drafted Framework for Information Literacy for Higher Education.